Usulan Perbaikan Kualitas Produk Kaus Polo dengan Menggunakan New Seven Tools dan 5W+2H (Studi Kasus: PT. Langgeng Sentosa Garmindo) - Agung Gumelar Fathurohman; Dewi Shofi Mulyati (UNISBA Press, 2023)
Abstract. PT. Langgeng Sentosa Garmindo is a company that produces apparel with one of its products being polo shirts. The problem that is being faced by the company is related to product quality, it is known that during quality inspections product defects are often found so that it needs to be reworked. Quality problems are reinforced by data on the number of product defects that still exceed the tolerance for defects by 1%. Product quality problems can be identified by the causes of the problems with the New Seven Tools method and the proposals with 5W+2H. The identification results obtained are for the sewing part which is the focus of repair with the causes of defects including lack of supervision from supervisiory, absence of periodic machine maintenance schedules, lack of knowledge about thread requirements, operators pursuing high wages, absence of work SOP reminders, absence of special operator training, unused items not being immediately disposed of and the company's climate is hot. The results of the proposed improvement of the 5W+2H method include making machine maintenance and cleaning schedules, making checksheets to carry out machine maintenance activities, giving instructions to supervisors to carry out strict supervision, increasing understanding of work instructions and providing motivation, making displays, making samples of calculating yarn requirements, making operator training schedules, making checksheets for machine conditions and disposing of or moving damaged machines, as well as cleaning building ventilation and adding temperature control devices in the form of exhaust fans. Keywords: New Seven Tools, Product Quality, 5W+2H. Abstrak. PT. Langgeng Sentosa Garmindo merupakan sebuah perusahaan yang memproduksi pakaian jadi dengan salah satu produk yang dihasilkannya adalah kaus polo. Masalah yang sedang dihadapi oleh perusahaan berkaitan dengan kualitas produk, hal tersebut diketahui ketika pemeriksaan kualitas sering dijumpai kecacatan produk sehingga perlu dilakukan rework. Permasalahan kualitas dikuatkan dengan data jumlah kecacatan produk yang masih melebihi toleransi kecacatan sebesar 1%. Permasalahan kualitas produk dapat diidentifikasi penyebab-penyebab masalahnya dengan metode New Seven Tools serta usulannya dengan 5W+2H. Hasil identifikasi yang didapatkan yaitu bagian sewing yang menjadi fokus perbaikan dengan penyebab kecacatan diantaranya kurangnya pengawasan supervisor, tidak adanya jadwal perawatan mesin berkala, kurang mengetahui mengenai kebutuhan benang, operator mengejar capaian upah tinggi, tidak adanya pengingat SOP kerja, tidak adanya pelatihan khusus operator, barang yang tidak terpakai tidak segera dibuang dan iklim perusahaan yang panas. Hasil usulan perbaikan metode 5W+2H diantaranya membuat jadwal perawatan dan pembersihan mesin, pembuatan checksheet untuk melakukan aktivitas perawatan mesin, memberikan instruksi kepada supervisor untuk melakukan pengawasan ketat, meningkatkan pemahaman instruksi kerja dan pemberian motivasi, pembuatan display, pembuatan contoh perhitungan kebutuhan benang, pembuatan jadwal pelatihan operator, pembuatan checksheet kondisi mesin dan melakukan pembuangan atau pemindahan mesin rusak, serta pembersihan ventilasi gedung dan penambahan alat pengatur suhu yang berupa exhaust fan. Kata Kunci: New Seven Tools, Kualitas Produk, 5W+2H.